2000
DOI: 10.1088/0022-3727/33/12/318
|View full text |Cite
|
Sign up to set email alerts
|

Simple method for characterizing synthetic graphite powders

Abstract: A simple method for characterizing synthetic graphite powders is presented in this paper. A thick glass cylinder contains a known weight of material, which is held between two conducting pistons. These allow the measurement of the electrical conductivity of the sample, and enable its compaction. The graphite powder is gently pressed, and its volume and conductivity variation are simultaneously measured. From these results, the relation between conductivity and the volume fraction of grains is derived: an equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
(22 reference statements)
4
16
0
Order By: Relevance
“…4,5 Here the percolation threshold of composites filled with graphite fillers has been estimated 10,11 according to procedures described in details in Refs. [15][16][17][18][19], based on either percolation or on effective-medium theories. All the size/geometry data of used graphite fillers along with the estimated percolation thresholds are gathered in Table II.…”
Section: Electromagnetic Characterizationmentioning
confidence: 99%
“…4,5 Here the percolation threshold of composites filled with graphite fillers has been estimated 10,11 according to procedures described in details in Refs. [15][16][17][18][19], based on either percolation or on effective-medium theories. All the size/geometry data of used graphite fillers along with the estimated percolation thresholds are gathered in Table II.…”
Section: Electromagnetic Characterizationmentioning
confidence: 99%
“…Moreover, even assuming that the actual geometry and inclusion size are well characterized, existing percolation theory generally only predicts a range for v c . 13 This range becomes more dubious given the challenge of accurately accounting for certain behavior on a microscopic behavior, such as particle-to-particle interaction or particle alignment, which can alter v c .…”
Section: Model Development and Assessmentmentioning
confidence: 99%
“…13,15 For our initial fits, we assumed that A should be fixed for a given inclusion aspect ratio, so we set it to different values and determined best-fit values of s and t for each experimental frequency and volume fraction of the SS and iron sphere data. For these calculations, we assumed σ = 1.4 × 10 6 S/m and 1 × 10 7 S/m for SS and iron, respectively.…”
Section: Model Development and Assessmentmentioning
confidence: 99%
“…In a previous work dealing with ellipsoidal particles having an infinite range of sizes and semi-axes a = b = c (Celzard et al 2000), application of EMT to anisotropic particles was shown to lead to the following expression of the percolation threshold:…”
Section: Connectivity Thresholdmentioning
confidence: 99%
“…In the case of ellipsoids of revolution, called spheroids, i.e., with principal semi-axes such that a = b = c, the depolarization factors obey L a = L b = 1/2 (1 -L c ), and always L a + L b + L c = 1. A figure showing the way L a and L c change with the aspect ratio of the spheroids may be found in Celzard et al (2000). For a prolate ellipsoid, i.e., such that a = b \ c (see Fig.…”
Section: Connectivity Thresholdmentioning
confidence: 99%